Fanatisme dan Fan War Penggemar Kpop di Media Sosial Tiktok - Rahmitha Fitri Ariyani; Ramadhani, Rizky Wulan; Widiastiana Vista Wijaya; Cholidah Astri Pertiwi (Kinesik, 2024)
Kpop fan groups are considered to have fanatical attitudes. Their fanaticism is shown through fandom war (fan war) which is interpreted as a dispute between two or more fan groups (fandoms). Fan wars are carried out through various social media including Tiktok. This study aims to determine the fanaticism and fan war of Kpop fans on Tiktok. This study uses a qualitative approach by interviewing five informants who carry out fan wars on Tiktok, namely PO, LY, NN, RF, and RK. The researcher also conducted observations and documentation. The data collected were then analyzed using Symbolic Interactionism Theory. The results of the study show that fan wars on Tiktok are carried out by writing comments or creating content with symbols that are mutually understood among members of the fan group. These symbols become the identity or "self" attached to a fan group. This identity becomes a source of pride as well as ridicule from other fan groups during fan wars. Fan groups on Tiktok are dominated by teenagers who are easily provoked. They do not re-check the truth of the information and end up spreading the content so that more and more people are involved in the fan war.